PERAN PROGRAM KEWIRAUSAHAAN DALAM PEMBERDAYAAN EKONOMI SANTRI DI PONDOK PESANTREN ROUDLOTUN NAFI’IYAH TEMPEL - M Sabiq Al Hadi; Nazila, Intan Putri (Yayasan Pendidikan Islam Amal Shaleh Kombongan, 2024)
This study aims to identify the role of Islamic boarding schools (pesantren) in cultivating modern entrepreneurial ventures and understanding the specific business units developed at Pesantren Roudlotun Nafi’iyah Tempel. Islamic boarding schools are recognized as institutions with potential for fostering an entrepreneurial culture, emphasizing the development of religiously devout and independent individuals, in line with entrepreneurship programs. Entrepreneurial skills are crucial in pesantren to ensure that students are not only competent in religious matters but also economically self-reliant, contributing significantly to the economy by fostering entrepreneurs among the students. With numerous pesantren and a large student population, these institutions hold strategic potential to support national economic development, particularly through the growth of modern industrial entrepreneurship. The research methodology employed in this study is qualitative, utilizing observation, interviews, and documentation at Pesantren Roudlotun Nafi’iyah Tempel. Findings indicate that Pesantren Roudlotun Nafi’iyah Tempel plays a significant role in cultivating modern entrepreneurial ventures, establishing various business units such as garment manufacturing, workshops, and student-run shops, engaging students and the community through entrepreneurship programs to enhance their well-being and create employment opportunities. Student involvement in entrepreneurship at Pesantren Roudlotun Nafi’iyah Tempel has successfully educated alumni to establish their own businesses